Pengaruh Penerapan Manajemen Operasional Saat Pandemi di PT. Pabrik Kertas Tjiwi Kimia Tbk. - Rizqi Anantia; Ricko Marthin; Alexander; Nico Hadi; Vivi Sonata (Politeknik Ganesha Medan, 2023)
In this era of globalization which is full of competition, fast and practical technological developments have helped increase efficiency in completing work. The positive impact of this development is also felt in the company's operations. By implementing good operational management, companies can improve efficiency, production effectiveness, and meet consumer needs. This study aims to analyze the effect of implementing operational management before and after the COVID-19 pandemic at PT. Pabrik Kertas Tjiwi Kimia Tbk. This type of research is qualitative with a document study research method with data collection in the form of documents and archives. With the arrival of the COVID-19 pandemic, it is possible that it will affect the performance of operational management. From the results of research on all management projects that have been implemented, such as project management that predicts a decrease or increase in the impact of a pandemic, by continuing to improve and adjust in terms of service, product quality, designing the right strategy, and using technology systems properly such as MRP and ERP . The results of this research are expected to provide an understanding of how paper companies face the challenges of the COVID-19 pandemic and to what extent their operational management can adapt. As for suggestions for further research such as reviewing operational management strategies in other companies with different approaches but still in the same field to provide more insight for paper companies in improving their operational management performance.